"Objechałem całą prawie Szwajcarię". Helweckie inspiracje w twórczości Czesława Miłosza - Wolski, Jan (Tematy i Konteksty, 2011)
Czesław Miłosz visited Switzerland many times and his contact with this Alpine republic – its citizens and customs – was undoubtedly inspiring for his works. This inspiration took shape of both poems and essays. His letters and memoirs fulfill the knowledge of literary history interested in earlier experiences of the Nobel Prize laureate. Miłosz’s sojourns in Switzerland usually can be linked to the crucial moments of his life and thus any references to the experiences of Mickiewicz seem more than obvious. The observations of majestic Alpine landscape encouraged the poet to reconcile himself to his fate due to the fact that the indestructibility of laws of nature is considered an opposition to fragile human existence. Miłosz is also concerned not only with the question of unity of European tradition based on the Catholic religion, but also with similarity of experiences in various parts of the continent. Therefore Switzerland functions as a symbol that confirms the fascination of the poet with beauty of the world and emphasizes the importance of revelations in human life.